A validity assessment of the Progress out of Poverty Index (PPI)™. (April 2015) - Desiere, Sam; Vellema, Wytse; D'Haese, Marijke
Highlights: PPI™ is promoted for poverty measurement in development programs. PPI™ by design satisfies four of the five criteria of SMART indicators. In this paper performance of the fifth criterion, Relevance, was analyzed. We conclude PPI™ accurately distinguishes poor from non-poor households. But lacks sensitivity to changes in poverty status. Abstract: Development organisations need easy-to-use and quick-to-implement indicators to quantify poverty when requested to measure program impact. In this paper we assess the validity of the Progress out of Poverty Index (PPI)™, a country-specific indicator based on ten closed questions on directly observable household characteristics, by its compliance to the SMART criteria. Each response receives a pre-determined score, such that the sum of these scores can be converted into the likelihood the household is living below the poverty line. We focus on the PPI scorecard for Rwanda, which was validated using two national household surveys conducted in 2005/06 and 2010/11. The PPI is Specific, Measurable, Available cost effectively, and Timely available. Yet, its Relevance depends on the way it is used. Although it accurately distinguishes poor from non-poor households, making it a useful reporting tool, its limited sensitivity to changes in poverty status restricts its usefulness for evaluating the impact of development projects.